Innovating Building Refurbishments: Embracing Global Digital Transformation for Today’s Construction Industry (International Journal of Scientific Research and Management (IJSRM), 2024)
The Uberization of the construction industry is a clear indication that the sector is gradually shifting towards the digital era. This transformation signifies a significant digitization of construction, incorporating smart technology in various phases, from design and planning to execution, operations, and management. This paper delves into the importance of embracing digital technologies in building refurbishments to meet the evolving demands of today’s construction landscape. By integrating innovative digital solutions such as Building Information Modelling (BIM), Internet of Things (IoT), artificial intelligence, robotics, and other cutting-edge technologies, refurbishment projects can achieve cost-effectiveness, precision, and environmental sustainability. The benefits of this digital shift encompass improved project coordination, safety, cost efficiency, and environmental impact management. However, challenges like high initial costs, resistance to change, cybersecurity threats, and skill shortages persist. The digital transformation is also shaped by global trends such as urbanization, population growth, and the push for smart, sustainable cities. Governments and private sectors acknowledge the potential of digital construction in meeting these demands more effectively. Thus, the industry must adapt to these technological advancements to stay competitive and address future infrastructure needs. The primary goal of this paper is to underscore the importance of embracing global digital transformation in building refurbishments, offering insights and recommendations for stakeholders in the construction sector to leverage digital technologies effectively for enhanced project outcomes and long-term sustainability. This study aims to explore the global digitalization of building construction, examining how advanced technologies like Building Information Modelling (BIM), Artificial Intelligence (AI), and the Internet of Things (IoT) are revolutionizing construction processes. By identifying the main drivers of digitalization in the construction industry, assessing the role of emerging technologies, and evaluating the benefits such as enhanced efficiency, cost savings, improved safety, and sustainability, this paper aims to showcase the necessity of digitalization to meet modern demands effectively. These abstract outlines the key concepts discussed in the paper, highlighting the advantages of integrating digital tools in building refurbishments, the obstacles, and opportunities in digital transformation within construction, and the potential impact on sustainability and project outcomes. Through case studies and industry insights, the study will demonstrate how digitalization is vital for staying abreast of modern requirements. Additionally, it will analysis case studies and successful implementations of digital technologies in refurbishment projects to illustrate best practices and lessons learned.